Disease burden and clinical severity of the first pandemic wave of COVID-19 in Wuhan, China - Yang, Juan; Chen, Xinhua; Deng, Xiaowei; Chen, Zhiyuan; Gong, Hui; Yan, Han; Wu, Qianhui; Shi, Huilin; Lai, Shengjie; Ajelli, Marco; Viboud, Cecile; Yu, Prof Hongjie (Nature communications, 2020)
The novel coronavirus disease 2019 (COVID-19) was first reported in Wuhan, China, where the initial wave of intense community transmissions was cut short by interventions. Using multiple data sources, here we estimate the disease burden and clinical severity by age of COVID-19 in Wuhan from December 1, 2019 to March 31, 2020. Our estimates account for the sensitivity of the laboratory assays, prospective community screenings, and healthcare seeking behaviors. Rates of symptomatic cases, medical consultations, hospitalizations and deaths were estimated at 796 (95% CI: 703–977), 489 (472–509), 370 (358–384), and 36.2 (35.0–37.3) per 100,000 persons, respectively. The COVID-19 outbreak in Wuhan had a higher burden than the 2009 influenza pandemic or seasonal influenza in terms of hospitalization and mortality rates, and clinical severity was similar to that of the 1918 influenza pandemic. Our comparison puts the COVID-19 pandemic into context and could be helpful to guide intervention strategies and preparedness for the potential resurgence of COVID-19. Here the authors analyze disease burden and clinical severity of COVID-19 during the first wave in Wuhan, China in comparison to past influenza virus pandemics and COVID-19 in the US and Canada. These estimates of symptomatic cases, medical consultations, hospitalizations and deaths should guide preparedness for this disease.